How correctional officers experience inmates suicidal behavior?: qualitative research and development of the model of a house - Lavrič, Meta (The prison journal, 2022)
As first responders in prisons, correctional officers are more exposed to suicides than the general population. The aim of the study was to explore how they experience the suicidal behavior of inmates and how they cope with potential psychological consequences of these experiences. We conducted interviews with 11 male correctional officers working in 12-h shifts, and analysed the data using a grounded theory approach. Results were conceptualised in The Model of a House, which consists of five parts representing different aspects of the experience. The model provides an overall understanding of how correctional officers experience the suicidal behavior of inmates.